أبو الأعلى المودودي ودوره في الدفاع عن الإسلام - بن الشهية, نزيهة; بن عمر, زينب; حنكة, آسيا; ونيسي, مارية (My University, 2019)
الملخص يدكر ىذا البحث حكؿ العمؿ الإسلبمي المنظ مف خلبلو ظير العديد مف الدعاة كالمصمحيف, أمثاؿ أبي الأعمى المكدكدم كالذم أنمكذجا فريدا لمداعية الإسلبمية, كبظيكر عدد كبير مف المؤسسات التعميمية الدينية تمثمت بقيا جماعة إسلبمية, كخدمة الدعكة الإسلبمية في العصر الحاضر. Summary This research revolves around the organized Islamic work through which many preachers and reformers appeared, such as Abi Al-A'la Al-Mawdudi, a unique example of the Islamic preacher, and the emergence of a large number of religious educational institutions represented by the establishment of an Islamic group and the service of Islamic da'wa in the present age.
دعوة